IMPLEMENTASI PROGRAM KELAS UNGGULAN DALAM MENINGKATKAN HASIL BELAJAR BACA KITAB SISWA DI MTS MADRASATUL QUR AN TEBUIRENG JOMBANG - Muhammad Haidar Agil Hasyimi; Burhanuddin Ridlwan; Laily Masruroh (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Implementation of the program as an innovation for educational institutions to use in developing learning objectives. Madrasas use superior class programs to be able to improve students' book reading learning outcomes to increase insight into the science of tools in reading books. The superior class program is specialized in nahwu shorof lessons and book reading practice using the al miftah method. Researchers determined 3 research focuses: 1). What is the form of the superior class program at Mts Madrasatul Qur'an Tebuireng Jombang, 2). What are the results of students' learning to read books at Mts Madrasatul Qur'an Tebuireng Jombang, 3). How does the superior class program improve student book reading learning outcomes at Mts Madrasatul Qur'an Tebuireng Jombang. In line with the title of the research, the researcher obtained the following research results: 1). Book reading learning activities include nahwu and shorof for 10 hours each week, learning nahwu and shorof for 2 hours each day while practicing reading books for 5 hours each week. 2). With the existence of superior class programs, madrasas can make students focus more on learning to read books that are in line with the goals of the madrasah so that they can improve student learning outcomes. 3). The superior class program has a positive impact on the learning outcomes of students who have talents and abilities, especially in the field of reading books, so that it is well facilitated.